Entitas histopatologi penderita perdarahan uterus terkait gangguan hormonal di Laboratorium Patologi Anatomi Rsup Sanglah tahun 2014 -2018 - Ida Ayu Eugenia Natasha Blanco Oka; IGA Sri Mahendra Dewi; Herman Saputra; Indraguna Pinatih; Indraguna Pinatih (Intisari Sains Medis, 2019)
Introduction: Dysfunctional uterine bleeding (DUB) is a major cause of a significant burden of health care for women, their families, and the community as a whole, leading to high morbidity for women who experience it. The purpose of this study is to determine the prevalence, characteristics of patients, and histopathological description in patients with DUB. Method: This study uses a secondary data analysis method in the medical record data of patients with DUB who has been histopathologically examined at the Anatomy Pathology Laboratory, Sanglah General Hospital Denpasar in the period 2014 to 2018.Result: From the period 2014 to 2018, 24 cases of DUB were found, the highest number was found in the pre menopause age (41-50 years) in 15 cases (62.5%), based on the type of estrogen related bleeding hormonal disorders in 17 cases (70.8%), and 7 cases of progesterone related bleeding (29.2%). The most histopathological type in the estrogen related bleeding group was 13 disordered proliferative phases (54.2%). In the group with progesterone related bleeding, the highest histopathological picture was irregular shedding in 5 cases (20.8%).Conclusion: Estrogen related bleeding pattern still dominating the histopatological pattern in the dysfunctional uterine bleeding at Pathology Anatomy Laboratory, Sanglah General Hospital period 2014-2018.